Health Information, Treatment, and Worker Productivity: Experimental Evidence from Malaria Testing and Treatment among Nigerian Sugarcane Cutters - Andrew Dillon; Jed Friedman; Pieter Serneels (Institute for the Study of Labor (IZA), 2014)
Agricultural and other physically demanding sectors are important sources of growth in developing countries but prevalent diseases such as malaria adversely impact the productivity, labor supply, and occupational choice of workers in these sectors by reducing physical capacity. This study identifies the impact of malaria on worker earnings, labor supply, and daily productivity by randomizing the temporal order at which piece-rate workers at a large sugarcane plantation in Nigeria are offered malaria testing and treatment. The results indicate a significant and substantial intent to treat effect of the intervention – the offer of a workplace based malaria testing and treatment program increases worker earnings by approximately 10% over the weeks following the mobile clinic visit. The study further investigates the effect of health information by contrasting program effects by workers revealed health status. For workers who test positive for malaria, the treatment of illness increases labor supply, leading to higher earnings. For workers who test negative, and especially for those workers most likely to be surprised by the healthy diagnosis, the health information also leads to increased earnings via increased productivity. Possible mechanisms for this response include selection into higher return occupations as a result of changes in the perceived cost of effort. A model of the worker labor decision that includes health perceptions in the decision to supply effort suggests that, in endemic settings with poor quality health services, inaccurate health perceptions may lead workers to misallocate labor thus resulting in sub-optimal production and occupational choice. The results underline the importance of medical treatment but also of access to improved information about one's health status, as the absence of either may lead workers to deliver lower than optimal effort levels in lower return occupations.
Keywords: I12; J22; J24; O12; 330; labor productivity; labor supply; malaria; randomized experiment